2017
DOI: 10.1242/jeb.149997
|View full text |Cite
|
Sign up to set email alerts
|

Early life experience drives short-term acclimation of metabolic and osmoregulatory traits in the leaf-eared mouse

Abstract: We studied the putative effect of early life experience on the physiological flexibility of metabolic and osmoregulatory traits in the leaf-eared mouse, Phyllotis darwini, an altricial rodent inhabiting seasonal Mediterranean environments. Adult individuals were collected in central Chile and maintained in breeding pairs. Pups were isolated after weaning and acclimated to different temperatures (cold or warm) and water availability (unrestricted and restricted) until adulthood. Subsequently, individuals were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Despite that studies on nongenetic inheritance mechanisms across multiple generations have increased (Donelson et al, 2016;Shama et al, 2016;Thor & Dupont, 2015), it is still unclear the impact and duration of transgenerational effects (see Burggren, 2015). Phenotypic plasticity during early ontogeny may induce the emergence of new phenotypes (Bartheld, Artacho, & Bacigalupe, 2017;Cavieres et al, 2016Cavieres et al, , 2017Kingsolver et al, 2015;Koussoroplis, Pincebourde, & Wacker, 2017). In flies reared at 28 V, more heat tolerant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite that studies on nongenetic inheritance mechanisms across multiple generations have increased (Donelson et al, 2016;Shama et al, 2016;Thor & Dupont, 2015), it is still unclear the impact and duration of transgenerational effects (see Burggren, 2015). Phenotypic plasticity during early ontogeny may induce the emergence of new phenotypes (Bartheld, Artacho, & Bacigalupe, 2017;Cavieres et al, 2016Cavieres et al, , 2017Kingsolver et al, 2015;Koussoroplis, Pincebourde, & Wacker, 2017). In flies reared at 28 V, more heat tolerant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Parallelly, it has been reported that the nature of thermal variability shape TPC in ectotherms (Cavieres, Bogdanovich, Toledo, & Bozinovic, ; Kingsolver, Higgins, & Augustine, ; Kingsolver & Woods, ). As such, TPCs differ depending on physiological tolerance to environmental thermal conditions, and the thermal history experienced by each phenotype (Bozinovic, Medina, Alruiz, Cavieres, & Sabat, ; Cavieres, Nuñez‐Villegas, Bozinovic, & Sabat, ; Huey & Berrigan, ; Huey et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with many phenotypic traits, these variations in energetic parameters may be accomplished by genetic differentiation, phenotypic flexibility, ontogenetic plasticity, or a combination of these mechanisms (Cavieres et al, 2017;Cheviron et al, 2013;Garland & Adolph, 1991). Phenotypic flexibility (i.e.…”
Section: Introductionmentioning
confidence: 99%